Impact of Emergence of Corporate Retailing on Small Traders a Case Study of Belagavi City: Understanding the Impact of Corporate Retailing on Small Traders in Belagavi City (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The organized retail sector is the most important addition to the Indian Economy at present, the organized sector accounts for only 2 to 4 percent of the total market. The economist intelligence unit forecasts that it would rise up to 25 to 30 percentages by 2020. So there is a tremendous growth in the organized retail sector. More more players are coming in the retail sectors with new attractive retail format like malls, Super market, Departmental stores etc. Many international retailers have entered Indian Market and many are about to enter to explore retailing opportunities now retailing business have been transformed into promising business worldwide. This sector contributes to 10 to GDP and contributes 8 to the employment sector. The object of study of this paper is to know the impact of upcoming corporate retail stores on the small and petty business organizations and to study the buying behavior of customers in the corporate retail shops. The survey work is conducted by preparing questionnaire.